Mapping and topographic localization of epitopes of the Yersinia pseudotuberculosis invasin protein. - Leong, J M (1991)
The Yersinia pseudotuberculosis invasin protein is a 986-amino-acid outer membrane protein that promotes bacterial penetration into mammalian cells by binding to beta 1-chain integrin receptors. We previously showed that the integrin binding domain is encoded by the carboxyl-terminal 192 amino acids. To further investigate the structure of this protein, we characterized a set of 32 monoclonal antibodies (MAbs) directed against invasin. Invasin deletion derivatives and fusion proteins carrying different segments of invasin were used to map the epitopes of this set of MAbs into 10 overlapping but distinct intervals. Indirect immunofluorescence of intact bacteria expressing invasin demonstrated that two large regions of invasin contain epitopes exposed on the bacterial surface. To assess the role of these surface-exposed regions in the binding and invasion of mammalian cells, each of the MAbs was tested for its ability to inhibit these processes. All of the MAbs that recognized bacterial surface-exposed epitopes in the cell binding domain of invasin inhibited both cell attachment and cell penetration, and no other MAbs inhibited either activity.